Reliability of Bahasa Malaysia version of family environment scale and its measurement issues - Omar, Khairani; Musa, Ramli; Haniff, Jamaiyah; Muhammad, Noor Azimah; Bujang, Adam; Mohamed Fadhlullah, Farihna (ASEAN Federation Of Psychiatry, 2010)
Objective: Family Environment Scale (FES) is one of the most widely used instruments to measure many family aspects. Cross cultural adaptation of the original FES is essential prior to local utilization as different cultures percept their family environments differently. We attempted to translate the FES into the Bahasa Malaysia language for adolescents, evaluate its reliability using internal consistency and compare its results with the original study. Methods: This is a cross-sectional study, involving adolescents aged 12-17 from four secondary schools. The adolescents were selected using quota sampling for different age, ethnic and academic performance. The study was divided into four phases, namely: i) translation of FES, ii) pilot test iii) internal consistency reliability test and iv) comparison of the study results with the original FES. Results: A total of 295 adolescents participated in this study. All of the reliability measurements generated (ranged between Cronbach’s alpha 0.10 - 0.70) were lower than those originally reported for this instrument (ranged between Cronbach’s alpha 0.61 -0.78). Five subscales in the Bahasa Malaysia version were found to be less than Cronbach’s alpha 0.5, which were below the acceptable level for practical or research use. There was considerable variation observed between the sample population of this study and that of the original study, which could be due to the social cultural differences. Conclusion: The Bahasa Malaysia version of FES requires further culturally appropriate revision. A new measuring scale could also be devised to provide an accurate evaluation of the family environment as perceived by Malaysian adolescents, which has acceptable levels of reliability and validity.